Livelihood and coping strategies among urban poor people in post-conflict period: Case of the Kathmandu, Nepal - Dahal, Kedar (Geographical Journal of Nepal, 2017)
Kathmandu is receiving large number of poor immigrants from the neighbouring districts. Many of them are living in the temporary or semi-permanent structure of dwelling on the bank of the river Bagmati and its tributaries. A traumatic experience of an unprecedented decade long armed conflict in Nepal between government security force and Maoist insurgents between 1996-2005 forced people migrate to the safer zones for their livelihood security, particularly in the urban areas like Kathmandu. As a consequence an increase in landlessness, joblessness, homelessness, livelihood insecurity, and disruption of the social fabric have been noticed. Now the country is in the post-conflict phase. This study, therefore, seeks to explore coping strategies of the poor people residing in Kathmandu in post-conflict phase by using primary data collected from sampled household based on multi-stage sampling procedures. Livelihood of the poor people is highly influenced by the armed conflict in the past. But the post-conflict phase is characterized by increasing mobility, expanding knowledge and opportunities. Working farther from the place of residence, change in food habits, mutual cooperation and borrowing are important coping strategies adopted by the poor people living in the poverty pockets. The Geographical Journal of Nepal Vol. 10: 73-88, 2017